Legal Regulation Prevention Of Child Marriage: The Perspective Of Lawrence M. Friedman and Sadd al-Dzarīʿah's Legal System - Aisyatul Azizah; Sudirman Sudirman; Isroqunnajah Isroqunnajah (Journal of Scientific Interdisciplinary, 2025)
This study examines the effectiveness of regulations preventing child marriage in the city of Surabaya after the enactment of Law No. 16 of 2019, which raised the minimum age for marriage to 19 years, but still allows for marriage dispensations through Article 7 paragraph (2). This normative loophole raises academic questions about how the law works in social reality and how preventive measures can be institutionalized. This study aims to assess the implementation of regional policies, particularly Perwali No. 32 of 2024, and to examine the practices of religious courts in deciding on marriage dispensations using Lawrence M. Friedman's Legal System Theory and the principle of Sadd al-Dzarīʿah as analytical tools. Empirical research methods were used through interviews, observations, documentation, and qualitative analysis of two cases of marriage dispensation that were rejected and granted. The results of the study show that the significant decrease in the number of marriage dispensations in Surabaya occurred due to the synergy of the legal structure (Religious Court, DP3APPKB, Ministry of Religious Affairs, RT/RW), legal substance through the Perwali which tightened procedures, and changes in the legal culture of society. The courts applied new standards that are more protective and based on maqāṣid al-syarī‘ah , making marriage dispensations an emergency mechanism rather than a legalization of child marriage. This study provides theoretical implications in the form of an integrative model between maqāṣid and the modern legal system, as well as practical implications in the form of recommendations to replicate the Surabaya model in other regions in an effort to protect children.